Archival Fictions : Materiality, Form, and Media History in Contemporary Literature - Benzon, Paul, 1976- (Book collections on Project MUSE., 2021)
"Technological innovation has long threatened the printed book, but ultimately, most digital alternatives to the codex have been onscreen replications. While a range of critics have debated the benefits and dangers of this media technology, contemporary and avant-garde writers have offered more nuanced considerations. Taking up works from Andy Warhol, Kevin Young, Don DeLillo, and Hari Kunzru, Archival Fictions considers how these writers have constructed a speculative history of media technology through formal experimentation. Although media technologies have determined the extent of what can be written, recorded, and remembered in the immediate aftermath of print's hegemony, Paul Benzon argues that literary form provides a vital means for critical engagement with the larger contours of media history. Drawing on approaches from media poetics, film studies, and the digital humanities, this interdisciplinary study demonstrates how authors who engage technology through form continue to imagine new roles for print literature across the late twentieth and early twenty-first centuries"--